Nursing care of a patient with thrombophlebitis of the upper limb (上肢血栓性静脉炎1例的护理) - DUAN Yixuan (段怡璇); YIN Kexin (尹可欣); E Haiyan (鄂海燕); HOU Jiejing (候洁婧); LI Jinhua (李金环); LIU Hongyan (刘红艳); XING Hui (兴慧) (Association of Integrative Nursing, 2021)
Phlebitis is a common complication of the intravenous infusion of fluids. The external application of Traditional Chinese Medicine plays an important role in the prevention and treatment of phlebitis. This paper reviewed the clinical data and nursing measures for a patient with thrombophlebitis of the upper limb. The external application with Chinese herbal medicine and potato slices was carried out to relieve the clinical symptoms and pain degree of patients. (静脉炎是静脉输液中较常见的并发症之一, 中药外敷在静脉炎的预防及治疗上发挥着重要作用。 本文总结1例双上肢血栓性静脉炎患者采用中药外敷治疗的效果, 通过选用中药外敷及土豆片贴敷联合治疗, 能够有效改善患者症状, 缓解患者疼痛。)